THE COMPLEXITIES ENCOUNTERED BY INDEPENDENT POWER PRODUCERS IN SMALL HYDRO POWER PROJECTS: A CASE STUDY OF HIMACHAL PRADESH IN THE INDIAN HIMALAYAN REGION. - Mehta, Arvuda (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian government has undertaken various initiatives aimed at fostering the growth of the small hydropower industry in collaboration with the private sector. However, despite these efforts, there has been a consistent decline in the proportion of hydropower within the overall energy mix over the years. Given this context, the primary objective of this article is to pinpoint the challenges and obstacles encountered by Independent Power Producers in the establishment of small hydropower projects in Himachal Pradesh. The study, conducted through a combination of primary and secondary sources, aims to identify the factors hindering the successful implementation of such projects. The findings of the study indicate that despite the introduction of a new hydro power policy by the state of Himachal Pradesh in 2006, aimed at unlocking the underutilized power potential by promoting private sector involvement in small hydropower generation, there persists a significant disparity between the available capacity and the installed capacity in the state. This gap can be attributed to a multitude of financial and non-financial challenges faced by Independent Power Producers through out the planning, construction and operations phases of their projects.